Verkhnee Gakvari: The contribution of adat, religious beliefs and public education to collective environmental management in an agro‐pastoral community in the Dagestan high Caucasus - G. Petherbridge; M. M. Ismailov; Sh. M. Ismailov; M. Kh. Rabadanov; A. A. Gadzhiev; A. A. Teymurov; M. R. Rabadanov; M. G. Daudova; A.-G. M. Abdulaev (Юг России: экология, развитие, 2021)
Aim. To examine the contribution structured systems of social mores (adat) and religious and secular public education have made to developing and sustaining socio‐ecological environment management in one community, Verkhnee Gakvari, in the upper valley of the Andiiskoe Koisu in the Dagestan Caucasus, from deep antiquity to the present day. Discussion. The research involved an extensive review of the relevant literature and on‐line resources dedicated of the region. Communities were visited across the region and discussions were undertaken with their representatives, as well as with other stakeholders. A particular emphasis was placed on the exemplary system of environmental education provided at the Verkhnee Gakvari School and its positive impact in sustaining the socio‐ecological production landscape of its territory. Significant progress was made in researching and documenting the range of issues fundamental to understanding the formation and continuity of the inter‐dependencies with nature and the cultural landscapes unique to these agro‐pastoral cultures of the upper Andiiskoe Koisu. This includes a comprehensive documentation of the contributions the Verkhnee Gakvari School has made to the preservation of its community’s socio‐ecological production landscape.Conclusion. Verkhnee Gakvari and other traditional communities of the upper Andiiskoe Koisu present a unique multi‐millenial cultural continuum of global significance for understanding the evolution of human society and are a remarkable survival in Europe of successful and harmonious socio‐ecological production landscape interdependencies. As the combined impacts of modern society and climate change now inevitably impinge upon the ability of the inhabitants of this ancient homeland to sustain the benefits which they have so successfully crafted from their environment, the region is in priority need of national and international recognition and support.